2008
DOI: 10.1155/2008/304965
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Operating Grids Through Delegated MatchMaking

Abstract: Abstract. The grid vision of a single computing utility has yet to materialize: while many grids with thousands of processors each exist, most work in isolation. An important obstacle for the effective and efficient inter-operation of grids is the problem of resource selection. In this paper we propose a solution to this problem that combines the hierarchical and decentralized approaches for interconnecting grids. In our solution, a hierarchy of grid sites is augmented with peer-to-peer connections between sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…In another work, we have investigated the existence of batches of jobs in grids, and found that in several real grids batches are responsible for 85%-95% of the jobs, and for 30%-96% of the total consumed CPU [30]. The imbalance of job arrivals in multi-cluster grids has been assessed using traces from the GWA in another study [31].…”
Section: Research In Grid Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, we have investigated the existence of batches of jobs in grids, and found that in several real grids batches are responsible for 85%-95% of the jobs, and for 30%-96% of the total consumed CPU [30]. The imbalance of job arrivals in multi-cluster grids has been assessed using traces from the GWA in another study [31].…”
Section: Research In Grid Resource Managementmentioning
confidence: 99%
“…The contents of the GWA have also been used to evaluate the performance of various scheduling policies, both in real [5] and simulated [35,31]environments. Finally, the tools in the GWA have been used to provide an analysis back-end to a grid simulation environment [31].…”
Section: Research In Grid Resource Managementmentioning
confidence: 99%
“…Iosup et al have introduced the concept of delegated matchmaking, where resources from remote Condor pools can be bound temporarily to the local environment [22]. The solution augments a hierarchy of Grid sites with peer-to-peer connections between sites on the same hierarchy level.…”
Section: Capacity Planning In Modern DCI Environmentsmentioning
confidence: 99%
“…Iosup et al [18] proposed a matchmaking mechanism for enabling resource sharing across computational Grids. Wang and Morris [37] investigated different strategies for load sharing across computers in a local area network.…”
Section: Related Workmentioning
confidence: 99%